Pentingnya Pendidikan Karakter Di Zaman Serba Digital SDIT Ibadurahman Ciruas - Wilda Andriani; Fadli Rahdiat Gunadi (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Character education is a process in which religious, moral, and ethical values are implemented to students through science, with the help of parents and teachers, as well as the community where it is very urgent to shape and develop the character of students. Each child has expectations The good things from him exist on this earth, but that hope must continue to be honed and socialized properly so that the character of each child can be formed and developed optimally. In this era that is all digital, children can use media so easily digital. The digital era which does not have a positive impact, but also has a negative impact in the end makes it a separate task for educators, parents as well as adults in providing guidance as well as monitoring what children have done with the digital media they use, right up to the child's able to take advantage of his digital media as well as possible also receive positive benefits for himself and his life later.